Suze Orman's Money Class [videorecording (DVD)] - Orman, Suze (PBS distribution, 2011)
Suze Orman gives her views on how to secure a hopeful and sustainable future in today's economy. After the upheavals of recent times, she believes that it's necessary to rethink many traditional strategies for financial success.